PFM.21 Treatment in fetal lower urinary tract obstruction: a prospective registry. (9th June 2014) - Morris, RK; Middleton, LJ; Malin, GL; Quinlan-Jones, E; Daniels, JP; Khan, KS; Deeks, JJ; Kilby, MD
Abstract : Objective: Describe the influences on decision making in fetal lower urinary tract obstruction (LUTO) and identify prenatal prognostic features. Methods: The PLUTO study included a registry of cases of isolated LUTO with conservative management or vesicoamniotic shunting (VAS). Logistic regression analysis examined prognostic features affecting outcome. For comparison of effectiveness the outcomes were survival to 2 years and renal function. Results: 45 women were registered, 78% (35/45) received conservative management. 27 women entered the registry due to clinician preference for an intervention (23 conservative, 4 VAS. Eighteen due to a patient preference for an intervention (12 conservative, 6 VAS. Influences will be explored further. Women in the conservative registry group were more likely: to have normal liquor volume at diagnosis (>5 th centile) (p = 0.05) and have a later diagnosis >24 weeks compared to randomised group (p = 0.003). These variables were associated with improved survival to 28 days in a mutivariable logistic regression analysis. At two years there was 20% (2/10) alive in the shunt group and 66% (23/35) in the conservative, RR 0.30 (95% CI 0.09, 1.08) p = 0.01. At 2 years in both groups 14 had normal renal function (one in shunt, 13 in conservative). There was a high false positive antenatal diagnosis rate in the conservative group (24%, 5/21 v 0% in shunt) as noted by postnatal diagnosis. Conclusion: The majority of fetuses in the registry had conservative management, associated with better outcomes. A significant proportion of prenatal cases had normal liquor, gestational age >24 weeks and false positive diagnosis.